The Effect of Progressive Muscle Relaxation on Blood Pressure Stability in Hypertension Patients - Ainal Mardhiah; Isni Hijriana (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a major global challenge, contributing to the burden of heart disease, stroke and kidney failure, as well as causing early death and disability. This study was to determine the effect of progressive muscle relaxation on blood pressure stability in hypertension patients. The method used was a quasi-experimental pre-and post-test group design without a control group. The sample was 35 hypertension patients using a consecutive sampling technique data analysis using the paired t-test. Participants were excluded if they were receiving other treatments for hypertension or had musculoskeletal conditions, such as joint diseases or fractures, while those who had a history of hypertension within the previous 12 months, were not taking antihypertensive medication, and were not undergoing any other therapeutic interventions were included. Participants were excluded if they were receiving other treatments for hypertension or had musculoskeletal conditions, such as joint diseases or fractures, while those who had a history of hypertension within the previous 12 months, were not taking antihypertensive medication, and were not undergoing any other therapeutic interventions were included. Based on the results of the bivariate analysis, it was found that there was an effect of progressive muscle relaxation on the stability of blood pressure in hypertension patients (P value = 0.000 <0.05). Conclusions: Progressive muscle relaxation can reduce tension in the body, and increase the relaxation response. When the body feels the relaxation response, it will slow down the heart rate so that pumping blood throughout the body becomes effective and blood pressure decreases.